2013
DOI: 10.1136/bmj.f4836
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of severe H1N1 infection in children presenting within Pediatric Emergency Research Networks (PERN): retrospective case-control study

Abstract: Objective To identify historical and clinical findings at emergency department presentation associated with severe H1N1 outcome in children presenting with influenza-like illness.Design Multicentre retrospective case-control study.Setting 79 emergency departments of hospitals associated with the Pediatric Emergency Research Networks in 12 countries.Participants 265 children (<16 years), presenting between 16 April and 31 December 2009, who fulfilled Centers for Disease Control and Prevention criteria for influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…Vandepitte et al reported that, older age, having an underlying co-morbidty and a history of being premature were risk factors for influenza infection in logistic regression anlysis [17]. In another study, Dalziel et al showed that a history of chronic lung disease, history of cerebral palsy / developmental delay are significantly associated with severe infection in children with ILI [18]. Because of the low frequency of H3N2 positivity in our study, it was difficult to evaluate risk factors in this study group.…”
Section: Discussionmentioning
confidence: 99%
“…Vandepitte et al reported that, older age, having an underlying co-morbidty and a history of being premature were risk factors for influenza infection in logistic regression anlysis [17]. In another study, Dalziel et al showed that a history of chronic lung disease, history of cerebral palsy / developmental delay are significantly associated with severe infection in children with ILI [18]. Because of the low frequency of H3N2 positivity in our study, it was difficult to evaluate risk factors in this study group.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognized that influenza viruses exchange genetic material, (reassortment) either emerging as a new strain, as we continue to see with H5N1 [16,[23][24][25], H1N1 [26][27][28], and now the latest H7N9 [3,4,29,30]. But this likely holds true for other viruses, as recently demonstrated with a novel coronavirus, most recently referred to as Middle East Respiratory Syndrome (MERS CoV) [11,12].…”
Section: Selected Epidemics and Emerging Pathogens -Respiratory Illnessmentioning
confidence: 99%
“…The spread of pulmonary infections occurs readily from both the upper and lower respiratory tracts (Figure 1) How respiratory illnesses spread [6,[26][27][28] Droplets Proximity (Less than 6 feet social distancing especially) Environment (overcrowding for example) Fomites Mucosa Prior immunity (or lack thereof) Poor hygiene Inherent transmissibility of pathogen (Ro)…”
Section: Selected Epidemics and Emerging Pathogens -Respiratory Illnessmentioning
confidence: 99%
“…This global network can answer questions with very infrequent outcomes, conduct studies that are generalisable across many settings, compare management across countries and health systems and develop international consensus. The first global PERN study, on the epidemiology of the H1N1 epidemic, was led by a PREDICT researcher and published in the British Medical Journal . Further PERN studies on toxicology, child traumatic stress and bronchiolitis management are in the data collection or the late concept phase.…”
Section: Competing Interestsmentioning
confidence: 99%
“…The first global PERN study, on the epidemiology of the H1N1 epidemic, was led by a PREDICT researcher and published in the British Medical Journal. 26 Further PERN studies on toxicology, child traumatic stress and bronchiolitis management are in the data collection or the late concept phase.…”
mentioning
confidence: 99%